Scientific and methodological bazes of formation of emotional intellegence in the educational process - Qodirova, Odina (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
This article deals with the human intellect and emotional intelligence, which is one of its types. In today’s rapidly evolving society, the development of individual emotional intelligence in the educational process is one of the most pressing issues. A high level of Emotional Intelligence allows a person to develop more effectively on personal and professional plans, manage stress, and communicate effectively with others. Working on developing it teaches us to understand the origin of at least some of our unconscious actions